Design and development of a dynamic-active cloth washing process - Heap, Yee Nean (Universiti Malaysia Perlis, 2011)
This thesis describes washing performance of a new introduced washing process. A laboratory washing model is developed to simulate the dynamic-active cloth washing process. It is the mechanical washing principle which combines deflection and abrasion actions due to hydrodynamic and impact water jet working liquid to wash the cloth. Complex dynamic fluid motion creates direct interaction between working liquid and washed cloth hence produce active washing. In the washing machine research area, engineer is interested in improving the washing performance by investigating its washing time, temperature and the mechanical action that depend on motion of rotating force or agitation effect acting on the washed cloth. The purpose of this study is to find the major contributing factor to optimum washing of the washing process. Data comparison in term of the washing efficiency has been performed between the laboratory developed model and the commercial washing machine modelled Samsung WA91U3. Result shows that the most significant factor contributes to optimum washing for developed model is washing time while the commercial washing machine depends major on the washing speed. Soil removal test indicates dynamic-active cloth washing process of developed laboratory model is about 50% more efficient than the current washing machine compared.